Perbedaan Konsentrasi Perekat Antara Briket Bioarang Tandan Kosong Sawit Dengan Briket Bioarang Tempurung Kelapa Terhadap Waktu Lama Membara - Muzi, Ilham; Mulasari, Surahma Astri (STIKES Wira Husada Yogyakarta, 2015)
ABSTRACT Some types of alternative energy sources can be developed into biomass energy. The potential of biomass wastes consisting of sugar cane plantations, oil palm, coconut, rubber, coffee and chocolate can be processed into briquettes bioarang. In briquetting bioarang, as the glue requires powdered charcoal and influence calorific value. This study was to determine differences in the provision of adhesive concentration on oil palm empty fruit bunches bioarang briquettes and coconut shell for a long time burning. This research is to design experiments Static Group Comparisons. The object of this research is the briquettes bioarang empty fruit bunches of palm and coconut shell with adhesive concentration of 600 cc, 700 cc, 800 cc and 900 cc to know a long time burning. ANOVA test briquettes bioarang palm empty fruit bunches with sig 0.000